PENGEMBANGAN MODEL REALISTIC MATHEMATICS EDUCATION PADA PEMBELAJARAN OPERASI BILANGAN BULAT, KPK, DAN FPB DI SD - Alben Ambarita (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2012)
Abstract:  The purpose of this research and development was to improvea quality of teaching mathematic material of integer, KPK, and FPB. Location of the research was in the SDN Metro centre, east, south, north, and west. Subjects were fifth grade elementary schools' students and teachers. Steps of of the research were: preeliminery study; development of RME model, and test the RME model. Data was collected by teachers and students' activity instruments, media, questionnaire, and test. The collected data was analized by qualitative and quantitative analysis. The research found teaching Realistic Mathematics Education model improved students' activities and learning outcomes. Students' learning motivation positively increased and also their achivement increased. Abstrak: penelitian pengembangan ini bertujuan meningkatkan kualitas pembelajaran matematika materi bilangan bulat, KPK, dan FPB.  Lokasi penelitian di SDN Metro Pusat, Timur, Selatan, Utara, dan Metro Barat dengan subjek penelitian guru dan siswa kelasV. Tahap-tahap penelitian meliputi studi pendahuluan, pengembangan model RME, dan pengujian model RME. Teknik pengumpulan data menggunakan instrumen aktivitas siswa dan guru, penggunaan media, angket, dan tes. Data dianalisis secara kualitatif dan kuantitatif. Hasil penelitian menunjukkan pembelajaran model Realistic Mathematics Education dapat meningkatkan aktivitas dan hasil belajar siswa. Motivasi belajar siswa tumbuh positif dan prestasinya meningkat secara signifikan.